2018
DOI: 10.1590/1980-5373-mr-2018-0324
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Rapid Microwave Sintering Process on the Electrical Conductivity, Thermal Conductivity and Mechanical Properties of Al-TiC Composites

Abstract: In this research, electrical conductivity, thermal conductivity and mechanical properties of the Al-TiC composites which were sintered via microwave-assisted process were investigated. The specimens were sintered for 3, 5 and 8 minutes. The results have shown that the sample which contains 4 vol. % TiC and was sintered for 8 minutes, has the highest electrical and thermal conductivities among the other obtained ones. Besides that, the sample which contains 8 vol. % TiC and was sintered for 3 minutes, has dedic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The change in resistance with increase in C content depends mainly on the arrangement or distribution of atoms in the film or in their structure [27]. The electrons are bonded firmly with the nucleus in the carbides, so unable to move freely and thus reduce the conductivity [28]. This can be explained further with their XPS analysis in future.…”
Section: Xrd Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The change in resistance with increase in C content depends mainly on the arrangement or distribution of atoms in the film or in their structure [27]. The electrons are bonded firmly with the nucleus in the carbides, so unable to move freely and thus reduce the conductivity [28]. This can be explained further with their XPS analysis in future.…”
Section: Xrd Analysismentioning
confidence: 99%
“…These could have influenced the decrease of surface resistance across the films. A higher value of ideality factor is commonly observed in the heterostructures of two different materials having large lattice mismatch [28]. This high value may also arise from image force and surface effects such as surface charges and an interfacial dielectric layer between the metal and the semiconductor.…”
Section: Influence Of C Content On Dc Conductivitymentioning
confidence: 99%
“…The sample with 20 mmol/L PDA shows the highest conductivity of approximately 1.55 × 10 7 S/m, which is comparable to other literature values. For example, Yaghobizadeh et al fabricated Al samples using microwave sintering and reported an electrical conductivity of 1.51 × 10 7 S/m. It is hypothesized that an appropriate amount of PDA can enhance the binding between Al and Cu NPs, while excessive PDA can be detrimental because of the lower conductivity of carbonized PDA than Al …”
Section: Resultsmentioning
confidence: 99%
“…Sintering aluminum (Al) and alloys is usually difficult because of several challenges, including poor flowability, high thermal diffusivity, surface oxidation layer, etc. Specifically, an oxide layer spontaneously formed on an Al surface, which is typically a few nanometers thick, , can prevent fusion of Al powder particles during a typical sintering practice such as pressureless sintering. Various methods have been used to promote sintering of Al alloys, including the introduction of reducing agents (e.g., H 2 ), spark plasma sintering, and microwave sintering. Nevertheless, improving the sinterability of the feedstock powders is essential for the successful fabrication of sintered Al components. Powders with better sintering behavior will also benefit various powder-based additive manufacturing processes of Al alloys such as binder jetting, direct paste printing, and selective laser melting/sintering.…”
Section: Introductionmentioning
confidence: 99%
“…There is a possibility that local overheating can lead to rounding of the sharp corners of the particles of the hard phases during a field-assisted sintering process. The structure formation of ceramic particle-reinforced aluminium matrix composites obtained by field-assisted sintering is the subject of recent publications [48][49][50][51][52][53][54][55][56][57][58]. Poor wettability between the metal matrix and the ceramic reinforcement leads to the formation of difficult-toeliminate porosity at the interfaces.…”
Section: Recent Trends In the Selection And Design Of Reinforcements ...mentioning
confidence: 99%